Dynamics of irregular migration: The Psycho-Philosophical irony in the global perception of equality - Onebunne I, Jude; Ojiakor-Umenze, Ifeoma; Onwuatuegwu N, Ignatius (COMMICAST, 2024)
This research aims to explore the dynamics of irregular migration as a psycho-philosophical irony in the quest for practical global equality. The research explores three fundamental issues in irregular migration bordering on the characteristics of migrants, the causes and motives of migrants, and the relationship of irregular migration with global perceptions of equality. Drawing on the Neo-Classical migration theory by Hicks (1932) and the Dual Labor Market theory by Ravenstein (1889), this study establishes that the unequal distribution of capital and labor at the macro level that leads to inequality in living conditions is a major factor of all migration. The study identifies that the characteristics and motives of migrants are identical to the problems associated with low socio-economic status which are the main drivers of migration. Furthermore, the study asserts that areas characterized by irregular migrants are consistent with the Human Capital Development Index (HCDI) classification that prioritizes living standard conditions across countries. As a benchmark, the HCDI supports the theoretical basis for high irregular migration in these regions triggered by the imbalance between countries at the lower end of the index and those at the top of the HCDI.  It is suggested that the global policy on aid to poor countries should lean towards domestication of capacity building in such countries to improve living standards and employment and to mitigate the current global antithesis caused by terrorism and insecurity whose impact is unfavorable to world peace.